2021
DOI: 10.1155/2021/8124593
|View full text |Cite
|
Sign up to set email alerts
|

Sex Variations in the Oral Microbiomes of Youths with Severe Periodontitis

Abstract: Objective. Periodontitis is an inflammatory disease of microbial etiology caused primarily by dysbiosis of the oral microbiota. Our aim was to compare variations in the composition of the oral microbiomes of youths with severe periodontitis according to gender. Methods. Subgingival plaque samples collected from 17 patients with severe periodontitis (11 males and 6 females) were split for 16S rRNA gene sequencing. The composition, α-diversity, and β-diversity of the patients’ oral microbiomes were compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…These in vivo data clearly suggest that these bacteria can synergistically alter the host's immune competence with the increased production of virulence factors (i.e., P. gingivalis virulence factors decrease the host response) by subverting innate-immune signaling [38]. Thus, a sex-specific difference in the induction of immunity correlates with sex-specific differences in the oral microbiome and the clinical severity and incidence of PD among women and men [15]. High-throughput miRNA profiling documented 190 DE miRNAs in male mandibles and 188 DE miRNAs in female mandibles.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These in vivo data clearly suggest that these bacteria can synergistically alter the host's immune competence with the increased production of virulence factors (i.e., P. gingivalis virulence factors decrease the host response) by subverting innate-immune signaling [38]. Thus, a sex-specific difference in the induction of immunity correlates with sex-specific differences in the oral microbiome and the clinical severity and incidence of PD among women and men [15]. High-throughput miRNA profiling documented 190 DE miRNAs in male mandibles and 188 DE miRNAs in female mandibles.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, men have a stronger inflammatory response to bacterial infection and greater osteoclast-driven alveolar bone resorption (ABR) than women [14]. Moreover, a recent study also reported sex-specific differences in the oral microbiome in patients with severe periodontitis [15].…”
Section: Introductionmentioning
confidence: 99%
“…SHHs can regulate the composition and behavior of oral microorganisms, which is an important factor in oral microbiomes dysbiosis. Previously, we revealed sex-based variations in the oral microbiomes with regard to periodontitis ( Zhao et al., 2021b ; Zhao et al., 2021a ). The dominant bacteria in males with severe periodontitis were those of the genera Pseudomonas and Papillibacter whereas, in females, they were from the genus Tannerella and order Fusobacteriales ( Zhao et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we revealed sex-based variations in the oral microbiomes with regard to periodontitis ( Zhao et al., 2021b ; Zhao et al., 2021a ). The dominant bacteria in males with severe periodontitis were those of the genera Pseudomonas and Papillibacter whereas, in females, they were from the genus Tannerella and order Fusobacteriales ( Zhao et al., 2021b ). For older patients with periodontitis, the predominant bacterial genus was Haemophilus in males and Campylobacter in females ( Zhao et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cardiovascular disease may be caused by periodontal disease via mechanisms such as inflammatory response, oxidative stress, immune response, and platelet aggregation (19, 30). Variations in the manifestations of dysbiosis have also been observed between patients of different sexes and between patients with or without dental caries/missing teeth (31,32). Studies have found that patterns of oral dysbiosis may induce the host's immune response (30); however certain pathogens may synergistically induce immunosuppression through an association with signaling pathways.…”
Section: Introductionmentioning
confidence: 99%